Innovative Directions in Children and Youth' Art Education - Savenkova, Lyubov G.; Radomskaya, Olga I. (International Review of Management and Marketing, 2016)
The article presents an innovative approach to children and youth' training and education. This approach is based on the students' integrated training and the polyart education. The authors examine the modern innovative educational programs. It is shown in the article that in the considered educational programs the experience is generalized of the art existence beginning from ancient times when the functions of art were different from the modern art. These programs are connected with educational archeology and cultural anthropology. The study of art takes into account the geographic, climatic, social factors of a region: an ecological approach ("ecology of culture" as the cultural environment of the personality development by D. Likhachev), national, regional and folk art traditions in family and society (L. Gumilev, G. Gachev). An attempt was undertaken to follow the inner, imaginative, spiritual connections of the word, sound, color, space, movement, shape, gesture at the level of the creative process. Keywords: polyart education, polyart innovative programs, integrative approach, the interaction of art, regional component, “here-and-now art”. JEL Classifications: O31, Z11